Pengelolaan Teknologi Tepat Guna dalam Meningkatkan Kualitas Sumber Daya Manusia Pengurus Posyantek yang Unggul - Budhi Prabowo; Elizabeth Tika Kristina H; Pusporini Palupi Jamaludin (Lembaga Pengembangan Kinerja Dosen, 2026)
This Community Service (PKM) activity aims to improve the quality of human resources (HR) among Posyantek administrators in North Serpong District through the management of Appropriate Technology (TTG). The challenge faced by partners is the limited understanding and skills of Posyantek administrators in managing and utilizing TTG optimally and sustainably. The implementation method included counseling, training, discussions, and hands-on practice related to Appropriate Technology management that aligns with the needs and potential of the local community. The results of the activity indicate an increase in the knowledge, skills, and professional attitudes of Posyantek administrators in TTG management. Furthermore, this activity also strengthened motivation and collaboration among Posyantek administrators in carrying out their role as technology facilitators at the sub-district level. This PKM activity was concluded to be effective in improving the quality of human resources among Posyantek administrators and is expected to have a long-term impact on Posyantek development and community empowerment based on Appropriate Technology in North Serpong District.